Affinity purification of sequence-specific DNA binding proteins. - Kadonaga, J T (1986)
We describe a method for affinity purification of sequence-specific DNA binding proteins that is fast and effective. Complementary chemically synthesized oligodeoxynucleotides that contain a recognition site for a sequence-specific DNA binding protein are annealed and ligated to give oligomers. This DNA is then covalently coupled to Sepharose CL-2B with cyanogen bromide to yield the affinity resin. A partially purified protein fraction is combined with competitor DNA and subsequently passed through the DNA-Sepharose resin. The desired sequence-specific DNA binding protein is purified because it preferentially binds to the recognition sites in the affinity resin rather than to the nonspecific competitor DNA in solution. For example, a protein fraction that is enriched for transcription factor Sp1 can be further purified 500- to 1000-fold by two sequential affinity chromatography steps to give Sp1 of an estimated 90% homogeneity with 30% yield. In addition, the use of tandem affinity columns containing different protein binding sites allows the simultaneous purification of multiple DNA binding proteins from the same extract. This method provides a means for the purification of rare sequence-specific DNA binding proteins, such as Sp1 and CAAT-binding transcription factor.